2015
DOI: 10.1080/00986445.2015.1017638
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Equilibrium Analysis of Propane Dehydrogenation with Carbon Dioxide and Side Reactions

Abstract: A thermodynamic analysis of propane dehydrogenation with carbon dioxide was performed using constrained Gibbs free energy minimization method. Different reaction networks corresponding to different catalytic systems, including non-redox and redox oxide catalysts, were simulated. The influences of CO 2 /C 3 H 8 molar ratio (1-10), temperature (700-1000 K) and pressure (0.5-5 bar) on equilibrium conversion and product composition were studied. In the presence of CO 2 with a molar ratio of CO 2 /C 3 H 8 =1, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…32,33 Coke formation (eq 2-10) is one of the major causes of deactivation of the catalysts for CO 2 −ODHP. 34 This reaction is endothermic and not a spontaneous reaction at room temperature because of its highly positive Gibbs free energy. However, it becomes spontaneous starting from ∼400 °C (i.e., ΔG 400°C = −6.5 kJ mol −1 ), resulting in catalyst deactivation in turn.…”
Section: Thermodynamic Analysis Of Oxidative Dehydrogenation Of Propa...mentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Coke formation (eq 2-10) is one of the major causes of deactivation of the catalysts for CO 2 −ODHP. 34 This reaction is endothermic and not a spontaneous reaction at room temperature because of its highly positive Gibbs free energy. However, it becomes spontaneous starting from ∼400 °C (i.e., ΔG 400°C = −6.5 kJ mol −1 ), resulting in catalyst deactivation in turn.…”
Section: Thermodynamic Analysis Of Oxidative Dehydrogenation Of Propa...mentioning
confidence: 99%
“…In addition, the decomposition reactions are one of the major causes of severe catalyst deactivation through coking, with the extent varying depending on the catalysts used. For example, the decomposition reaction (eq ) dominates and causes severe deactivation in the case of Fe–Ce solid solution catalysts, while the cracking reaction (eq ) may occur on precious Pt catalysts. , Coke formation (eq ) is one of the major causes of deactivation of the catalysts for CO 2 –ODHP . This reaction is endothermic and not a spontaneous reaction at room temperature because of its highly positive Gibbs free energy.…”
Section: Thermodynamic Analysis Of Oxidative Dehydrogenation Of Propa...mentioning
confidence: 99%
“…Therefore, reducible metal oxides capable of activating CO 2 at lower temperatures could be potential candidates for this reaction. 18 Cerium(IV) oxide (ceria) is widely used in catalysis, primarily as a component of support materials for metal nanoparticles. However, it has been reported that ceria can be an effective catalyst in its own right for the oxidative dehydrogenation of ethylbenzene to styrene in the presence of CO 2.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There is, however, a tradeoff to operation of the reaction at higher temperatures (>550 °C), which favor combustion of both the reactants and products. Therefore, reducible metal oxides capable of activating CO 2 at lower temperatures could be potential candidates for this reaction …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, under such high temperatures, the undesirable side reactions such as hydrogenolysis, cracking and coke deposition are inevitable. 4,5 Currently, many studies are devoted to developing novel and potential catalysts in propane dehydrogenation (PDH), such as ceria-based catalysts, 6 calcined hydrotalcite-supported platinum catalysts, 7 Sn/SiO 2 catalysts, 8 Pd-based catalysts, 9 mesoporous carbons, gallium oxide-based catalysts 10,11 and so on. Among these, gallium oxide-based catalysts have been recognized as new promising alkane dehydrogenation materials due to their unique capability to activate hydrocarbon species and excellent catalytic efficiency as compared to conventional Cr 2 O 3and V 2 O 5 -based catalysts.…”
Section: Introductionmentioning
confidence: 99%